2017
DOI: 10.3892/etm.2017.4433
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-664 enhances proliferation, migration and invasion of lung cancer cells

Abstract: Altered microRNA (miR) expression serves an important role in the development and progression of lung cancer. In the present study, the effect of miR-664 on proliferation, migration and invasion of lung cancer cells was assessed. The proliferation of lung cancer cells with an overexpression of miR-664 was examined via MTT assay. The Caspase-Glo3/7 assay was used to examine the effect of miR-664 on cisplatin-induced apoptosis in lung cancer cells. The migration and invasion of lung cancer cells were assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…Studies have found that more than half of miRNAs are located in cancer-related genomic regions, suggesting that dysregulation of miRNAs possibly plays key roles in tumour occurrence and progression (12). Increasing number of studies have recently indicated that miRNAs are aberrantly expressed in various types of human cancers, such as lung cancer (13), bladder cancer (14), breast cancer (15) and gastric cancer (16). MiRNAs regulate diverse biological processes, especially those involved in critical pathways linked to cancer cell proliferation, cycle, apoptosis, metastasis, invasion and…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that more than half of miRNAs are located in cancer-related genomic regions, suggesting that dysregulation of miRNAs possibly plays key roles in tumour occurrence and progression (12). Increasing number of studies have recently indicated that miRNAs are aberrantly expressed in various types of human cancers, such as lung cancer (13), bladder cancer (14), breast cancer (15) and gastric cancer (16). MiRNAs regulate diverse biological processes, especially those involved in critical pathways linked to cancer cell proliferation, cycle, apoptosis, metastasis, invasion and…”
Section: Introductionmentioning
confidence: 99%
“…Liu and coauthors also demonstrated that this miRNA sensitized cells to cisplatin through targeting of the RAD51 gene [ 64 ]. A similar behavior in lung cancer cells [ 66 ] and in cervical cancer [ 67 ] has been shown for the up-regulated miRNA-664 that, when up-regulated, increases tumor proliferation and sensitivity to cisplatin through the modulation of E cadherin, vimentin, and Snail expression. Therefore, it could be hypothesized that the limited and unsuccessful efficacy of the platin-based pharmacological treatment may depend on a lack of correct stratification of patients on a genetic basis; probably the subset of patients with high levels of miRNA-506 or miRNA-664 could respond to cisplatin.…”
Section: Role Of Ncrnas In Csccsupporting
confidence: 61%
“…MicroRNAā€1296 can inhibit metastasis and epithelialā€mesenchymal transition of hepatocellular carcinoma by inhibiting SRPK1ā€mediated PI3K/AKT pathway (Xu et al, ). In lung cancer cells, microRNAā€664 is able to promote the tumor proliferation, migration, and invasion (Zhu et al, ). In our study, a novel microRNA target of DGCR5, hsaā€mirā€22ā€3p was identified through bioinformatics search and confirmed by dualā€luciferase reporter system.…”
Section: Discussionmentioning
confidence: 99%